2017
DOI: 10.1021/acs.chemmater.7b00776
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Hydrogen in Atomically Precise Gold Nanoclusters

Abstract: Hydrogen−metal interaction is the foundation of many technologies and processes, but how hydrogen behaves in atomically precise gold nanoclusters remains unknown even though they have been used in hydrogenation catalysis and water splitting. Herein, we investigate how hydrogen interacts with [Au 25 (SR) 18 ] q clusters and mono-atom-doped bimetallic [M 1 Au 24 (SR) 18 ] q clusters (M = Pt, Pd, Ag, Cu, Hg, or Cd) from first principles. We find that hydrogen behaves as a metal in these clusters and contributes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 71 publications
1
103
0
Order By: Relevance
“…On the other hand, Lee and Jiang et al investigated the effect of heteroatom doping of Au n (SR) m NCs on the HER activity. [28][29][30][31] They examined the HER activity of hexanethiolate (C6)protected Au 25 and PtAu 24 NCs in a tetrahydrofuran (THF) electrolyte containing 1.0 M triuoroacetic acid (TFA) ( Fig. 4A-C).…”
Section: Electrocatalytic Applications For Water Splittingmentioning
confidence: 99%
“…On the other hand, Lee and Jiang et al investigated the effect of heteroatom doping of Au n (SR) m NCs on the HER activity. [28][29][30][31] They examined the HER activity of hexanethiolate (C6)protected Au 25 and PtAu 24 NCs in a tetrahydrofuran (THF) electrolyte containing 1.0 M triuoroacetic acid (TFA) ( Fig. 4A-C).…”
Section: Electrocatalytic Applications For Water Splittingmentioning
confidence: 99%
“…These results are in good agreement with the DFT calculation results. In addition to these studies, Jiang et al, also investigated the doping effects of various elements (Pt, Pd, Ag, Cu, Hg, and Cd) in Au 25 (SCH 3 ) 18 using DFT calculations [105]. The results predicted that Au 24 Pt(SCH 3 ) 18 , Au 24 Pd(SCH 3 ) 18 , and Au 24 Cu(SCH 3 ) 18 , in which the heteroatom (Pt, Pd, or Cu) is located at the center of the metal core, have a higher HER activity than Au 25 (SCH 3 ) 18 .…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%
“…Fine nanoparticle catalysts suitable for the HER [88][89][90][91][92], OER [93][94][95], and ORR [96][97][98][99][100][101] have been developed based on theoretical predictions of activity volcano plots using various metals and alloy nanoparticles (NPs). Au n NCs have recently been observed to possess catalytic activity for the HER, OER, and ORR [77, [102][103][104][105][106][107][108][109][110][111][112][113][114][115][116] (Figure 1). Therefore, Au n NCs are expected to become a model catalyst even in such an energy conversion system.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies were employed to understand the hydrogen‐metal interaction in gold clusters. Jiang group investigated how hydrogen interacts with [Au 25 (SR) 18 ] q clusters from first principles, and found that hydrogen behaves like a metal in these clusters and contributes its 1s electron to superatomic free‐electron count . The same group also studied the hydrogen‐gold interaction in the phosphine‐protected Au 22 (L) 6 cluster [L = 1,8‐bis(diphenylphosphino)octane] with eight coordinatively unsaturated Au atoms .…”
Section: Recent Breakthroughmentioning
confidence: 99%